The Influence of Service Quality Dimensions on Member Satisfaction at Koperasi Serba Usaha (KSU) Syariah Surya Sekawan in Martapura, Banjar Regency, South Kalimantan Province - Audah, Ali; Kadir, Abdul; Fatih, Hardika Muhammad; Badrian, Badrian; Jahra, Pati Matu (Universitas Hang Tuah, 2025)
This study aims to analyze the influence of service quality dimensions, namely tangible, reliability, responsiveness, assurance, and empathy, on the member satisfaction of the Islamic Multipurpose Cooperative (KSU) Syariah Surya Sekawan in Martapura, Banjar Regency, South Kalimantan Province. The research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 cooperative members selected by purposive sampling. The data were analyzed using multiple linear regression. The results show that partially, the variables tangible (X1) and empathy (X5) have a significant effect on member satisfaction. Meanwhile, the variables reliability (X2), responsiveness (X3), and assurance (X4) do not have a significant partial effect. However, simultaneously, all five independent variables have a significant influence on member satisfaction, as indicated by the F-test result, where F count is 211.168 > F table 2.81, with a significance value of 0.000 < 0.05. The R Square value of 0.681 indicates that 68.1% of the variation in member satisfaction can be explained by the five service quality dimensions studied. These findings highlight the importance of holistic service quality management within Islamic cooperatives to enhance member satisfaction. Therefore, cooperative management is expected to improve physical service aspects and strengthen empathy-based approaches in service interactions.